Analysis of Print Speed Variations Effect and Nozzle Temperature on the Tensile Strength of 3D Printed TPU-95A Products - Gulo, Triadesman; Mardiyana, Dani; Sumarno, Dodi Iwan (Jurnal Konversi Energi dan Manufaktur, 2025)
This study aims to analyze the effect of print speed and nozzle temperature variations on the tensile strength of TPU-95A material printed using the fused deposition modeling (FDM) method. The varied parameters include print speeds (70, 80, and 90 mm/s) and nozzle temperatures (230 and 240 °C). Tensile test specimens were produced using an Ender-3 Pro 3D printer according to the JIS K6251-2017 standard and tested with a Shimadzu AGS-X 10kN tensile testing machine. The results showed that the combination of a 90 mm/s print speed and a 230 °C nozzle temperature yielded the highest tensile strength of 318.74 kgf/cm². Conversely, the lowest tensile strength of 212.20 kgf/cm² occurred at a 90 mm/s print speed and a 240 °C nozzle temperature due to thermal degradation of the material. This study highlights the importance of selecting optimal printing parameters to enhance the mechanical strength of 3D-printed products made from TPU-95A.